No North Sea : the Anglo-German evangelical network in the middle of the nineteenth century - Railton, Nicholas, 1957- (Studies in Christian Mission, 2000)
This volume deals with those Christians who helped construct an international and inter-denominational evangelical network in western Europe in the middle of the nineteenth century. The Evangelical Alliance (est. 1846) institutionalised this ecumenical impulse. The Berlin Conference (1857) was the high-point of cross-border cooperation in those decades. The réveil in France and Switzerland and the Erweckung in Germany laid the groundwork for the Alliance in Europe. England, the motherland of the evangelical revival, provided a resource centre for continental evangelicalism. The chapters on the various missionary endeavours at home and abroad draw attention to the outward-looking, charitable and evangelistic character of evangelicals. Students of evangelicalism, the missionary movement and the ecumenical movement will find the book to be of particular importance.